Malaria in Bulambya, Ileje district, south-west Tanzania - Maegga, BTA; Kalinga, AK; Chacha, SW; Kibona, M; Mwayawale, J; Jangson, K (Tanzania Journal of Health Research, 2006)
This study was carried out to determine malaria situation in Bulambya Division, Ileje district in southwest Tanzania. Outpatient attendance records from 1999 to 2002 were examined for malaria cases in eleven health facilities. A cross-sectional study to determine malaria prevalence and its potential vectors was done in May 2004. Blood samples were collected from 502 schoolchildren from 16 primary schools and examined microscopically for malaria parasites. Indoor resting mosquitoes were collected in ten houses in each of the ten villages covered. Health facility data for 1999 showed the highest (60.7%) and lowest (11.5%) annual malaria morbidity rates were recorded at Itumba and at Ibaba, respectively. Malaria parasitaemia rate among schoolchildren ranged from 0-36.7%; the lowest prevalence was observed in the high altitude mountainous range and the highest in the lower altitude plateaux. Of 1,504 mosquitoes caught, 205 (13.6%) were female Anopheles gambiae s.l., 215 (14.3%) An. funestus and 68.9% were culicines. Data from both health facility records and school surveys indicate that there is high malaria morbidity in the lower plateaux (1100 to =1350m), around Itumba and Isongole, where indoor anopheles mosquito densities were relatively higher than in the higher altitudes (>1,350 m) around Ibaba. In the lower altitude range, there was less malaria on steep slopes than on flat terrain. Further studies are recommended to closely monitor malaria situation in these epidemic prone highlands of southwest Tanzania. Tanzania Health Research Bulletin Vol. 8(1) 2006: 17-21